THE INTERACTIVITY OF ICT TOOLS - KORTAN, Michal; PROKÝŠEK, Miloš (Journal of Technology and Information Education, 2015)
This article deals with the concept of interactivity which, in course of time, became overused, not only in terms of information systems. Thus, the thesis also discusses the unclear interpretation of interactivity and aims to express more apt definition. The interactivity is analyzed across various fields, which further provides a basis for the establishment of unbiased model called classification frame defining a degree of interactivity of specified complex systems.
Keywords: Classification frame; complex system; HCI; interactivity